2009
DOI: 10.1253/circj.cj-09-0478
|View full text |Cite
|
Sign up to set email alerts
|

From the Ryanodine Receptor to Cardiac Arrhythmias

Abstract: Circ J 2009; 73: 1561 -1567 t is well known that contraction of the heart is signaled by an increase of intracellular calcium concentration ([Ca 2+ ]i) from a resting or diastolic level of approximately 100 nmol/L to peak systolic levels of approximately 1 μmol/L (see References 1-5 for reviews). A major factor determining the strength of the force of contraction is the amplitude of this systolic Ca transient; for example, the positive inotropic effect of β-adrenergic stimulation results from an increase of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 82 publications
0
59
0
2
Order By: Relevance
“…Intracellular Ca 2+ handling is a critical regulator of action potential duration, and mechanical activity of cardiomyocytes via excitation‐contraction coupling 9. Abnormalities in its homeostasis can therefore reduce cardiac output and potentially leading to mortality but also initiate arrhythmogenic triggers in the atrial or ventricular myocardium 10, 11, 12. Previous studies have reported that XO inhibition has beneficial effects on cardiac remodeling,13, 14, 15 mechano‐energetics16 and endothelial function17 both in experimental and clinical studies.…”
mentioning
confidence: 99%
“…Intracellular Ca 2+ handling is a critical regulator of action potential duration, and mechanical activity of cardiomyocytes via excitation‐contraction coupling 9. Abnormalities in its homeostasis can therefore reduce cardiac output and potentially leading to mortality but also initiate arrhythmogenic triggers in the atrial or ventricular myocardium 10, 11, 12. Previous studies have reported that XO inhibition has beneficial effects on cardiac remodeling,13, 14, 15 mechano‐energetics16 and endothelial function17 both in experimental and clinical studies.…”
mentioning
confidence: 99%
“…Causing the autosomal-dominant and recessive forms of CPVT, mutations in genes encoding cardiac ryanodine type 2 receptor (RYR2) and calsequestrin 2 (CASQ2) were found. [23][24][25] In this study CPVT was presented in early school age and the incidence of cardiac arrest or sudden death during the follow-up period was 40%. All patients with CPVT except 1 showed symptomatic improvement after treatment with a β-blocker (propranolol, metoprolol and atenolol), but the life-threatening events were not completely prevented.…”
Section: Discussionmentioning
confidence: 76%
“…17 As shown in Figure 1, the EAD and prolonged APD observed in dnNRSF myocytes were completely suppressed by a specific blocker of the NCX. Therefore, it appears reasonable to expect that intracellular Ca 2+ handling is also altered in dnNRSF myocytes.…”
Section: Intracellular Ca 2+ Transientmentioning
confidence: 76%